Internal stability of geosynthetic-reinforced soil walls in tiered configuration. Issue 2 (April 2011) - Yoo, C.; Jang, Y.S.; Park, I.J.
Abstract : ABSTRACT: This paper presents the results of an investigation into the internal stability of two-tier, geosynthetic-reinforced soil (GRS) walls. Model tests were first conducted using two-tier GRS model walls that were reduced from a full-scale GRS wall according to the similitude law. A series of finite element (FE) analyses were also carried out on full-scale GRS walls with various offset distances and reinforcement distributions. It is shown that the critical offset distance beyond which two tiers act independently set by the Federal Highway Administration (FHWA) design guideline is considerably larger than that obtained from the current study. Also shown is that the lower-tier reinforcement length has a greater effect on the overall wall stability than the upper-tier reinforcement length, as the minimum reinforcement length changes more drastically with the offset distance D for the lower tier than for the upper tier. Practical implications of the finding are discussed.